2011
DOI: 10.1016/j.jtcvs.2011.01.055
|View full text |Cite
|
Sign up to set email alerts
|

Intraradial administration of fasudil inhibits augmented Rho kinase activity to effectively dilate the spastic radial artery during coronary artery bypass grafting surgery

Abstract: Fasudil is a very effective Rho kinase inhibitor that deinhibits myosin light chain phosphatase and powerfully relieves vasospasm in situ in radial arteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Recently fasudil a rho kinase inhibitor has been found to be useful intra-radially to relieve its spasm. 32 In short, the current evidence states that SVG may compare well with RA in the patency rates during short term follow up, but definitely RA scores better in the long term. Also, RA use should be planned on the right coronary system only if there is high grade stenosis of the target vessel which supplies a large area of viable myocardium 33 and in younger men where they yield better results.…”
Section: Radial Artery (Ra)mentioning
confidence: 86%
“…Recently fasudil a rho kinase inhibitor has been found to be useful intra-radially to relieve its spasm. 32 In short, the current evidence states that SVG may compare well with RA in the patency rates during short term follow up, but definitely RA scores better in the long term. Also, RA use should be planned on the right coronary system only if there is high grade stenosis of the target vessel which supplies a large area of viable myocardium 33 and in younger men where they yield better results.…”
Section: Radial Artery (Ra)mentioning
confidence: 86%
“…28 Takagi et al investigated the effects of the ROCK inhibitor fasudil on radial artery graft vasospasm prevention. 65 Their findings showed an increase of in situ free blood flow with a corresponding decrease of myosin phosphatase targeting subunit 1 (MYPT1) and myosin light chain (MLC) phosphorylation that strongly counteracted the effects of major vasoconstrictors (NE and 5-hydroxytryptamine). Enhanced ROCK activity was also identified in skeletonized, spastic radial arteries as compared to nonmanipulated, nonspastic arteries, indicating that mechanical stimulation-induced vasospasm is likely mediated via the ROCK pathway as well.…”
Section: Insights From Btx-a Utility In the Treatment Of Raynaud's Phmentioning
confidence: 98%
“…In the fasudil group, 2 ml of fasudil solution (Asahi Kasei, Japan) diluted to 0.9 mg/ml (2.67 mmol/L) was injected. This concentration was determined according to a basic research that we performed previously [8]. In the papaverine group, 2 ml of papaverine (0.4 mg/ml or 1.0 mmol/L) mixed with heparinized blood was injected.…”
Section: Protocolmentioning
confidence: 99%
“…Therefore fasudil might protect endothelium from damage, thereby preventing intimal proliferation, acceleration of atherosclerosis and thrombosis, which likely improves the long-term patency of grafts. Our previous study [8] suggested that the antispastic effect of fasudil is due to blockade of Rho-associated protein kinase (ROCK), because intraluminal fasudil injection into RA abolishes the increase in myosin phosphatase targeting subunit 1 (MYPT1) phosphorylation at the ROCK phosphorylation site Thr 853 , and consequently deinhibits myosin light chain phosphatase.…”
Section: Commentsmentioning
confidence: 99%